Development of a Single Degree of Freedom Haptic System Handle - Kwa, Chin Kok (2004)
Sense of touch is one of the most important senses for human. Human feels and interacts with the environment through their sense of touch. This thesis describes the design and development of a single degree of freedom handle with force feedback. The interaction between the handle and the user is achieved through the usage of a DC servomotor. The servomotor provides the resistive force to the manipulator. To control the servomotor, electronics circuit is constructed. The electronics circuit controls the force provided by the motor by using the Pulse Width Modulation technique. A computer is used to provide graphical interface to the user. The computer is also used to control the force provided by the motor by sending data through its parallel port to the controlling electronics circuit. At the end of the project, a single degree of freedom handle has been constructed and its characteristics have been tested. From the tests conducted, the system built managed to provide resistive torque up to 1.6Nm